Enteric Salmonella or Campylobacter infections and the risk of inflammatory bowel disease. Issue 3 (29th December 2010) - Jess, Tine; Simonsen, Jacob; Nielsen, Nete Munk; Jørgensen, Kristian Tore; Bager, Peter; Ethelberg, Steen; Frisch, Morten
Abstract : Objective: Enteric pathogens have been implicated in the aetiology of inflammatory bowel disease (IBD), but increased rates of stool testing of patients with unclear gastrointestinal symptoms might cause detection bias. Hence, the objective of this study was to analyse incidence rates of Crohn's disease and ulcerative colitis among patients with Salmonella - or Campylobacter -positive and negative stool tests and to study the incidence of positive and negative stool tests among patients already diagnosed with IBD. Methods: The Danish population was followed for 94.3 million person-years during 1992–2008 using national registers to identify persons with positive and negative stool tests and patients with IBD. Using Poisson regression, incidence rate ratios (IRRs) for IBD after positive or negative stool tests and, conversely, IRRs for positive and negative stool tests following IBD, were calculated. Results: IRRs for IBD were significantly high in the first year after Salmonella - or Campylobacter -positive stool tests (IRRs 5.4–9.8), and they remained moderately increased 1–10 years later (IRRs 1.6–2.2), and less so >10 years later (IRRs 0.8–1.8). However, IRRs for IBD <1 year after a negative stool test were several-fold higher (IRRs 53.2–57.5), and a decreasing incidence pattern over time was parallel to that following positive test results. Among patients with IBD, IRRs for subsequent positive and—most notably—negative stool test results were also significantly high. Conclusion: Similarities in temporal risk patterns for IBD following positive or negative stool tests indicate that the increased occurrence of Salmonella - or Campylobacter -positive results around the time of first IBD hospitalisation results from detection bias.